Variation of stellar populations and dark matter with time and environment - Shetty, S (2017)
In this thesis, I probe the stellar and dark matter component of galaxies in order to infer their evolutionary histories. I am doing this by studying two distinct galaxy population samples: (i) a high redshift sample at z∼1, and (ii) a high density environment sample of galaxies in the nearby Coma cluster. By comparing these samples to a sample of galaxies in the local Universe in a low density environment, I infer variation in their properties as a function of time and environment. For both samples, I create accurate dynamical models to infer the stellar Mass-to-Light ratios of the galaxies and their dark matter fractions. Furthermore, I model the stellar population of the galaxies using a full-spectrum technique while reproducing their star formation history in a non-parametric manner. In addition, I use IFS data for a subset of galaxies in the high density sample to create detailed dynamical models that strengthen the results found in that sample. Based on the quantities derived from these analyses, I present results on the IMF normalisation and dark matter fraction of galaxies in both samples. Furthermore, I studied the scaling relations of these galaxies and compared them to that observed for the ATLAS3D sample, which serves as a low density sample of the Local Universe, to infer variation in galaxy properties as a function of time and environment.